Obstructive Sleep Apnea in Adults with Treacher Collins Syndrome is Related with Altered Anthropometric Measurements, Increased Blood Pressure and Impaired Quality of Life - Vilma Fidélis-da Silva, Leide; Henrique Kiemle-Trindade, Sergio; Noel Marzano-Rodrigues, Maria; Hollara Medeiros, Laís; Tonello, Cristiano; Kiemle Trindade-Suedam, Ivy (Sleep Science, 2023)
Objectives This study aimed at evaluating the risk for obstructive sleep apnea (OSA) and its frequency in adults with Treacher Collins syndrome (TCS). The association of OSA with excessive daytime sleepiness (EDS), respiratory symptoms, and clinical variables was also assessed.Material and Methods The subjects were prospectively screened for OSA through the Berlin Questionnaire and type I polysomnography. The Epworth Sleepiness Scale and the Respiratory Symptoms Questionnaire were used for assessing OSA-related symptoms. Quality of life was assessed by means of the Short Form 36 Health Survey.Results The sample comprised 20 adults with TCS (55.0% female), aged 22.6 ± 5.8 years. Mean values of systemic blood pressure (113.0 ± 12.6/68.0 ± 9.5mmHg), body mass index (22.9 ± 5.9kg/m2), neck (34.1 ± 4.3cm), and waist circumference (80.4 ± 13.6cm) characterized the sample. A high risk for OSA was detected in 35% of the sample. Polysomnography results indicated an OSA frequency of 44.4%, with a median apnea-hypopnea index (AHI) value of 3.8 events/hour (minimum = 0.2; maximum = 77.5). Snoring (75.0%), nasal obstruction (70.0%) and EDS (20.0%) were the reported OSA-related symptoms. Quality of life median scores were 72.3 points (minimum = 45.0; maximum = 91.1). Strong positive correlations between AHI versus waist circumference and AHI versus systolic blood pressure were found. Moderate positive correlations between AHI versus body mass index and AHI versus neck circumference were detected. Negative correlation between AHI versus vitality were also observed.Conclusion Adults with TCS are at high risk for OSA, which is associated with respiratory symptoms, altered anthropometric measurements, increased systolic pressure and impairment of quality of life.
Keywords: mandibulofacial dysostosis; airway obstruction; polysomnography